Stored energy predictions from dislocation-based hardening models and hardness measurements for tensile-deformed commercial purity copper - Čebron, Matjaž (Strojniški vestnik, 2014)
Stored energy analyses by differential scanning calorimetry (DSC) and indentation hardness measurement were performed on cross- sectional samples cut from the gauge length of tensile-deformed copper specimens. The stress-strain curve was described using dislocation- based hardening models integrated into a visco-plastic Taylor-type model of polycrystal deformation. Three approaches in reproducing the experimental stress-strain curve were used to evaluate the differences in dislocation density predictions resulting from different modelling options. A good description of hardening was achieved by all three approaches and constitutive models and only negligible differences were found in the predicted dislocation density between assumed homogeneous and heterogeneous dislocation distribution throughout the polycrystal. Measured values of stored energy are somewhat lower than those published in research studies in which one-step and slow annealing methods were used. A simple model predicting a nearly linear increase of stored energy with dislocation density was found to adequately describe retained energy evolution. Since different dislocation arrangements result in different yield stress and energy predictions, both results can be used to determine values of parameters in two-internal-variable hardening models. Even though both measured quantities were satisfyingly described, uncertainties regarding material parameters and the applied polycrystal and stored energy models prevent us from claiming that the evaluated dislocation density distributions represent the actual dislocation structure in the material. As expected for strongly hardening materials, the relationship between yield stress and hardness could not be adequately approximated by a linear function. Instead, a linear combination of yield stress and hardening rate was used, finally providing a relation between hardness and stored energy through their mutual dependence on yield stress.
Keywords: dislokacije; kalorimetrija; modeli deformacijskega utrjevanja; plastičnost kristalnih struktur; shranjena energija; trdota